2012
DOI: 10.1186/1471-2407-12-143
|View full text |Cite
|
Sign up to set email alerts
|

Serial selection for invasiveness increases expression of miR-143/miR-145 in glioblastoma cell lines

Abstract: BackgroundGlioblastoma multiforme (GBM) is the most common primary central nervous system malignancy and its unique invasiveness renders it difficult to treat. This invasive phenotype, like other cellular processes, may be controlled in part by microRNAs - a class of small non-coding RNAs that act by altering the expression of targeted messenger RNAs. In this report, we demonstrate a straightforward method for creating invasive subpopulations of glioblastoma cells (IM3 cells). To understand the correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 23 publications
1
38
0
1
Order By: Relevance
“…The other upregulated microRNA in highly aggressive GBM cell lines is microRNA-145 [30]. That fact promotes decreased proliferation and invasion of GBM cell lines [33].…”
Section: Candidate Micrornas For High-grade Gliomas Biomarkersmentioning
confidence: 99%
“…The other upregulated microRNA in highly aggressive GBM cell lines is microRNA-145 [30]. That fact promotes decreased proliferation and invasion of GBM cell lines [33].…”
Section: Candidate Micrornas For High-grade Gliomas Biomarkersmentioning
confidence: 99%
“…Evidence has also demonstrated malignant cells to exhibit widespread dysregulation of microRNAs compared to normal cells (Chan et al, 2005; Ciafre et al, 2005). A large number of subsequent studies have demonstrated a role for microRNAs in tumorigenesis (Chan et al, 2005; Ciafre et al, 2005; Esquela-Kerscher and Slack, 2006; He et al, 2005; Koo et al, 2012; Lavon et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Another microRNA with conflicting data regarding expression levels in GBM when compared to non-neoplastic tissues is miR-145 (Koo et al, 2012). Koo et al (2012) demonstrated miR-145 upregulation in a number of highly aggressive GBM cell lines (Koo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated the regulatory functions of miRNAs in RCC cell proliferation (11)(12)(13), apoptosis (14,15), invasion and metastasis (16)(17)(18). A predominant and systemic alteration in miRNA expression during renal carcinogenesis has been indicated by studies of miRNA expression profiling (16). miR-204 is an miRNA which is enriched in germline and mesoderm-derived tissues, such as the testis, uterus, kidney, lung, heart and bladder (19).…”
Section: Introductionmentioning
confidence: 99%